Current Status of SUMOylation Inhibitors - Brackett, Christopher M.; Blagg, Brian S.J. (Current Medicinal Chemistry, 2021)
SUMOylation has emerged as an important post-translational modification that involves the covalent attachment of the Small Ubiquitin-like Modifier (SUMO) polypeptide to a lysine residue of a target protein. The enzymatic pathway of SUMOylation is very similar to ubiquitinylation and involves an activating enzyme, a conjugating enzyme, ligases, and deconjugating enzymes. SUMOylation modulates the function of a number of proteins associated with various pathways, and in fact, dysregulation of the SUMOylation pathway is observed in both cancer and neurological diseases. In many cancers, the SUMO enzymes are upregulated, and SUMO levels correlate directly with prognosis and disease progression. As a result, there has been an emphasis on the discovery and development of inhibitors of SUMOylation. In this review, the latest advances in SUMOylation inhibitors are described alongside the methods used to discover small molecule SUMOylation inhibitors, which include natural products, peptidomimetics, as well as synthetic derivatives identified via virtual screens.
Keywords: SUMO